P378 Oxidative status and antioxidant capacity in children and adults with IBD: preliminary results of the OxIBDiet trial. (27th May 2021) - Gatti, S; Cianfruglia, L; Galeazzi, T; Palpacelli, A; Quattrini, S; Quatraccioni, C; Catassi, G; Monachesi, C; Di Sario, A; Armeni, T; Catassi, C
Abstract: Background: Redox imbalance is involved in several aspects of inflammatory bowel disease (IBD). The OxIBDiet (NCT04513015) is a multicentre, 2-phases project involving IBD children and adults with the following aims: 1. To evaluate oxidative status of IBD subjects. 2. To estimate the effects of an antioxidant diet in IBD patients. Preliminary results are shown in this abstract. Methods: The total antioxidant capacity, lipid peroxidation and the degree of protein oxidation were measured respectively through the ferric reducing ability of plasma (FRAP, µmol/equivalent FeSO4), serum levels of the thiobarbituric acid reactive substances (TBARs, µmol MDA) and advanced Oxidation Protein Products (AOPP, µmol/g protein). Reactive oxygen species (ROS, Arbitrary Units) and activities (nmol/min/mg of protein) of the main antioxidant enzymes, superoxide dismutase (SOD), glutathione peroxidase (GPX), glutathione reductase (GR), glutathione S-Transferase (GST) and catalases (CAT) were evaluated in PMNs cells. Oxidative stress markers were correlated with demographic variables and clinical parameters. Results: Fifteen adults (mean age: 36.2 ±11.4 years, 47% female, 67% in remission) and thirty five children (mean age: 14.13 ±2.2 years, 60% female, 65% in remission) with IBD have been enrolled so far. FRAP was significantly reduced in IBD children compared to healthy controls (median values: 212.1 vs. 248.3, p=0.0001) and to IBD adults (median value: 281, p<0.001), while no difference was observed between adults with IBD and the control group (p= 0.1). ROS levels did not differ in IBD children compared to adults and controls. The activity of GPX and CAT enzymes was increased in children with IBD in comparison to controls (p:0.02 and 0.001, respectively) while the activity of the other enzymes (GST, GR and SOD) and levels of lipid peroxidation and protein oxidation was not different between the 2 groups. Overall in the IBD group (children plus adults) FRAP was positively correlated with age (r=0.40, p=0.006), male gender (r=0.33, p=0.03) and use of biologics (r=0.47, p=0.001) and inversely correlated to disease activity based on clinical scores (r= -0.38, p=0.009). No correlation was found between FRAP and serum C-reactive protein or calprotectin levels. Conclusion: The total antioxidant capacity (FRAP) is significantly impaired in IBD children respect to IBD adults and to healthy controls, thus suggesting an early involvement of oxidative stress in IBD pathogenesis. Moreover, the activity of the main antioxidant enzymes (GPx and CAT) in IBD children is increased, as a possible compensation for redox imbalance. Final results will clarify the involvement of antioxidant cascade in IBD pathogenesis and in therapeutic approach.